THE EFFECT OF THE DISCOVERY LEARNING MODEL ON STUDENTS' LEARNING ACTIVITY IN ECONOMICS SUBJECTS AT SMA NEGERI 10 PALEMBANG - Rahmadona, Naila; Fatimah, Siti (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study aims to prove the influence of the discovery learning model on the learning activity of students in economics subjects at SMA Negeri 10 Palembang. Quantitative research method of experimental type with research design Pre- Experimental Design One Group Pretest-Posttest. The population in this study is class X of SMA Negeri 10 Palembang even semester for the 2024/2025 academic year which studies economics subjects with a class X.6 research sample of 35 students using cluster sampling techniques. The data collection techniques used were questionnaires and observations. The questionnaire was used to obtain data on learning activity and observation data was obtained from the results of observation during learning with the discovery learning model. The hypothesis test was carried out using a paired sample t test showing a count of 4.941 > a table of 1.691 which means that H0 is rejected and Ha is accepted so that there is an influence of the discovery learning model on the learning activity of students in economics subjects at SMA Negeri 10 Palembang. Educators are advised to optimize the Discovery learning model by ensuring that students follow each step appropriately and in a structured manner. Educators also need to pay attention to indicators of learning activity so that learning goals are achieved and students are actively involved in discussions and learning processes